2015
DOI: 10.1017/s1930297500005131
|View full text |Cite
|
Sign up to set email alerts
|

Reflective liberals and intuitive conservatives: A look at the Cognitive Reflection Test and ideology

Abstract: Prior research finds that liberals and conservatives process information differently. Predispositions toward intuitive versus reflective thinking may help explain this individual level variation. There have been few direct tests of this hypothesis and the results from the handful of studies that do exist are contradictory. Here we report the results of a series of studies using the Cognitive Reflection Test (CRT) to investigate inclinations to be reflective and political orientation. We find a relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
45
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 76 publications
11
45
5
Order By: Relevance
“…According to Jost 22 , using the same cognitive reflection test we used in the present study to assess analytic thinking, prior studies consecutively showed a marked difference between conservatives and liberals: 11 studies showed liberals perform better on the test, and only one study showed no difference along partisanship. In our study, pro-government voters had significantly lower analytic thinking ( M = 0.44, SD = 0.30) than anti-government voters ( M = 0.50, SD = 0.30, t (989) = − 3.47, p = 0.001, d = − 0.23), so it appears that pro-government voters relied much less on reflective thinking than those who would vote for any of the opposition parties 22 , 44 , 45 . However, it is not related to individual differences in intelligence, but rather the lack of motivation to use intellectual capacities on the conservative side of the political spectrum.…”
Section: Discussionmentioning
confidence: 97%
“…According to Jost 22 , using the same cognitive reflection test we used in the present study to assess analytic thinking, prior studies consecutively showed a marked difference between conservatives and liberals: 11 studies showed liberals perform better on the test, and only one study showed no difference along partisanship. In our study, pro-government voters had significantly lower analytic thinking ( M = 0.44, SD = 0.30) than anti-government voters ( M = 0.50, SD = 0.30, t (989) = − 3.47, p = 0.001, d = − 0.23), so it appears that pro-government voters relied much less on reflective thinking than those who would vote for any of the opposition parties 22 , 44 , 45 . However, it is not related to individual differences in intelligence, but rather the lack of motivation to use intellectual capacities on the conservative side of the political spectrum.…”
Section: Discussionmentioning
confidence: 97%
“…These methods can be easily implemented in future research on dual-process models, including experiments conducted online. Some of the commonly used reflection manipulations are recently shown to be ineffective (e.g., Deppe et al, 2015;Meyer et al, 2015), and earlier findings based on these manipulations often fail to replicate (e.g., Sanchez et al, 2017). Hence, previous results based on unreliable reflection manipulations should be tested using improved methods.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using intuition and reflection manipulations often do not directly test whether cognitive processes were activated in the intended directions. While some have checked the direct effects of their manipulations on cognitive performance (e.g., Deppe et al, 2015;Lawson et al, 2020;Yilmaz & Saribay, 2016), subjective self-report questions and behavioral measures such as response times are frequently relied on as alternative manipulation checks Yilmaz & Isler, 2019). The lack of performance measures would be misleading if, rather than thinking reflectively about the problem at hand, participants were to rely on their own lay theories about reflection (Saribay, Yilmaz & Körpe, 2020) or if they were to respond in socially desirable ways (Grimm, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inconsistencies in the literature are likely to stem in part from the unreliability of the methods used to activate reflective (or intuitive) thinking. For example, three different methods of manipulation used by Gervais and Norenzayan (2012) to prime reflective thinking (e.g., viewing pictures of Rodin's The Thinker or completing a sentence scramble task) failed manipulation checks in studies by Deppe et al (2015). Another technique -cognitive disfluency -used by Gervais and Norenzayan (2012) has been shown to be ineffective in activating reflective thinking in a high-powered study (Meyer et al, 2015), and in a Turkish sample (Yilmaz & Saribay, 2016).…”
Section: Introductionmentioning
confidence: 99%